Evaluation of Vocal Communication in a Robot Collective - İsmail Hakkı Parlak; Mehmet Dinçer Erbaş (Düzce Üniversitesi Bilim ve Teknoloji Dergisi, 2020)
In this research, we attempt to design a model in which multiple robots communicate with an artificial proto-language whose symbols are vocally encoded letters of the Morse alphabet. We have shown that, as the robots have limited sensing and acting abilities, the communicated symbols of the proto-language differentiates from their original versions due to copying errors. We check the effects of two distinct environmental factors, namely the positional distance between the robots and the amount of noise in the environment. It is shown that both of these factors affect, in different ways, how accurately the presented proto-language can be accurately transmitted by the robots.